Elevated Familial Cardiovascular Burden Among Adolescents With Familial Bipolar Disorder - Toma, Simina; Fiksenbaum, Lisa; Omrin, Danielle; Goldstein, Benjamin I. (Frontiers in Psychiatry, 2019)
Background: Bipolar disorder (BD) is among the most heritable medical conditions, and certain phenotypic characteristics are especially familial in BD. BD is also strongly associated with elevated and premature cardiovascular disease (CVD) morbidity and mortality. Thus far, little is known regarding the familiality of cardiovascular risk in BD. We therefore examined the extent of CVD-related conditions among relatives of: adolescents with BD with a family history of BD (familial BD), adolescents with BD without a family history of BD (non-familial BD) and healthy controls (HC). Materials and Methods: The sample included 372 adolescents; 75 with familial BD, 96 with non-familial BD, and 201 HC. Parents of the adolescents completed the CARDIA Family Medical History interview regarding the adolescents’ first- and second- degree adult relatives. We computed a “cardiovascular risk score” (CRS) for each relative, based on the sum of the presence of diabetes, hypertension, obesity, dyslipidemia, stroke, angina, and myocardial infarction (range 0-7). Primary analyses examined for group differences in mean overall CRS scores among first and second- degree relatives combined, controlling for age, sex and race. Secondary analyses examined first- and second-degree relatives separately, controlling for age, sex and race. Results: There were significant between-group differences in CRS in first- and second- degree relatives combined, as hypothesized: CRS was highest among adolescents with familial BD (1.14 ±0.78), intermediate among adolescents with non-familial BD (0.92 ±0.79) and lowest in HC (0.76±0.79; F=6.23, df=2, p=002, p2=.03). There was a significant difference between adolescents with familial BD and HC (p=0.002, Cohen’s d=0.49). A similar pattern of differences was identified when first-degree and second-degree relatives were examined separately. Limitations: familial cardiovascular burden determined based on parent interview, not evaluated directly. Conclusions: Adolescents with BD with a family history of BD have elevated rates of CVD-related conditions among their relatives. This may be related to genetic overlap between BD and CVD-related conditions, shared environmental factors that contribute to both BD and CVD-related conditions, or a combination of these factors. More research is warranted to better understand the interaction between familial risk for BD and CVD, and to address this risk using family-wide preventive approaches